Learning Platforms for Implementing Formative Interventions to Promote the Health and Safety of Workers in Brazil - Lopes, Manoela Gomes Reis; Vilela, Rodolfo Andrade de Gouveia; Silva-Macaia, Amanda Aparecida; Guirado, Vinícius Monteiro de Paula; Querol, Marco Antonio Pereira (Frontiers in Psychology, 2021)
Formative intervention methodologies, such as the Change Laboratory (CL), are increasingly being used in work environments. However, the learning process entailed in the application of these methodologies has received insufficient attention and may be facilitated through the use of learning platforms. We examined the development of learning and training strategies for implementing formative interventions, drawing on the experiences of a research group focusing on workers’ health. Information obtained from individuals involved in CL formative activities was analyzed and interpreted using Cultural-Historical Activity Theory and the theory of expansive learning. The process of learning to implement formative interventions unfolded gradually, beginning with the interventionists’ initial exposure to abstract concepts that they subsequently internalized via various mediations and applied in concrete situations. Four key interventionist training strategies used to foster collective learning were identified: (1) promoting dialogues and exchange of experiences, (2) creating environments for continuous learning and permanent discussion (seminars and post-graduate courses and the use of communication technologies), (3) creating spaces for experimentation and the practical application of concepts (case studies and participation in interventions), and (4) the use of the double stimulation method during training programs.